LITERATUR REVIEW: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IBU HAMIL MEMILIH MELAKUKAN PERSALINAN DI FASILITAS KESEHATAN DI INDONESIA - Aulia Zahara; Susilawati (CV. ADIBA AISHA AMIRA, 2023)
Childbirth is a physiological state experienced by everyone. However, these physiological conditions become pathological when the mother does not know these physiological conditions and helpers or nurses do not understand how physiological delivery should be and how to manage it in such a way as to reduce maternal mortality. The purpose of this study is how the factors that influence pregnant women in giving birth at health facilities and what the opinion of the mother's knowledge about it. By scanning the Google Scholar database for the terms